1984
DOI: 10.1002/art.1780270913
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose prednisone therapy in rheumatoid arthritis: effect on vitamin d metabolism

Abstract: It has long been recognized that treatment with glucocorticoids can produce a significant loss of bone mass (1,2). The mechanism for this steroid-induced bone loss is not fully understood. but is associated with a marked decrease in intestinal calcium absorption and an increased urinary calcium excretion that frequently accompanies administration of supraphysiologic doses of glucocorticoids (3.4).It has been proposed that steroid-induced alterations in vitamin D metabolism are responsible for the decrease in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Available data about the effect of glucocorticoids on vitamin D metabolism are, however, inconclusive. Serum levels of 25-hydroxyvitamin D were low in a number of studies (7) and normal in others (39). Serum 1,25(OH) 2 D 3 levels also varied between studies (1, 7, 32).…”
Section: Discussionmentioning
confidence: 91%
“…Available data about the effect of glucocorticoids on vitamin D metabolism are, however, inconclusive. Serum levels of 25-hydroxyvitamin D were low in a number of studies (7) and normal in others (39). Serum 1,25(OH) 2 D 3 levels also varied between studies (1, 7, 32).…”
Section: Discussionmentioning
confidence: 91%
“…Suppressed gene expression by GCs may be controlled by the transcriptional factor AP1 (21). The serum level of 1,25-dihydroxyvitamin D 3 was lower in some series and normal in others, and serum calcitriol level was also variable across studies (9,51,58). In addition, Braun et al (8) and Hahn et al (20) found that prednisone had little effect on serum dihydroxylated vitamin D levels in patients, whereas intestinal calcium absorption fell, suggesting that the GC-related impairment in calcium absorption may be independent of vitamin D. Therefore, reduced duodenal CaBP-9k is not due to suppression of vitamin D by Dex but is derived from the activation of GR by Dex attested with GR antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid induced osteoporosis is the results of a number of factors that adversely aŠect calcium homeostasis. [26][27][28][29] Systemic eŠects resulting in abnormalities in gonadal hormone secretion, calcium absorption, and renal handling of calcium and speciˆc eŠects of glucocorticoids on bone all contribute to bone loss. 30,31) In this study, bone calcium content and serum ALP activity were not reduced by glucocorticoid injections, although bone weight and protein contents were markedly reduced.…”
Section: Discussionmentioning
confidence: 99%